0354 Incidence of cardiovascular disease among danish firefighters – a cohort study. (21st August 2017) - Pedersen, Julie Elbæk; Petersen, Kajsa; Ebbehøj, Niels; Bonde, Jens Peter; Hansen, Johnni
Abstract : Objectives: To explore the incidence of selected diagnoses of cardiovascular diseases (CVD) among 11.691 male Danish firefighters, including the relative risk among different exposure groups. Methods: Trade unions, with firefighter membership records, Danish municipalities and private companies covering firefighting assignments supplied historical employment records to this study. The Supplementary Pension Fund Register, with information on all employees in Denmark, was used to establish two occupational reference groups: a) a random sample from the employed male population and b) the military. Information on CVD, 1977–2014, was retrieved from the Danish National Patient Registry. Age and calendar standardised incidence rates (SIR) were estimated using reference group rates. Results: The number of observed cases significantly exceeded the expected number for all cardiovascular diseases combined when firefighters were compared with both references. Significantly increased SIRs were also observed for angina pectoris (1.16, 95% CI=1.08–1.24), acute myocardial infarction (1.16, 95% CI=1.06–1.26), chronic ischaemic heart disease (1.15, 95% CI=1.06–1.24) and atrial fibrillation/flutter (1.25, 95% CI=1.14–1.36) compared with the general working population sample. When comparing the firefighters with the military, results reflected the same pattern. In subgroup analyses, the risk of CVD was elevated for full-time employed firefighters, but decreased with increasing duration of employment. Conclusion: Our study indicates a modest elevated CVD incidence among Danish firefighters. This study is the first large cohort study exploring the association between firefighting and CVD incidence, and more studies including more detailed information on "dose" of firefighting and potential confounding factors are warranted.